Cycling-related trauma admissions to the major trauma centre in the cycling capital of the United Kingdom. Issue 12 (December 2022) - Arshad, Zaki; Majeed, Malik; Thahir, Azeem; Anwar, Fahim; Rawal, Jaikirty; Hull, Peter; Carrothers, Andrew; Chou, Daud Tai Shan
Highlights: Helmet wearers were significantly older than non-wearers Helmet use was associated with a significantly lower risk of head injury and higher GCS score 'Fall from cycle' was the most common injury mechanism. 'Cyclist v Vehicle' collisions showed the most severe injury characteristics Future interventions could target driver and cyclist education and helmet promotion campaigns Abstract: Purpose: This study aims to characterise cycling related injuries presenting to a major trauma centre located within a region with the highest rates of cycling in the UK. Methods: A retrospective analysis of cycling related trauma admissions occurring between January 2012 and June 2020 was performed. Our institution's electronic patient record system was used to collect relevant data for analysis including age, gender, mechanism of injury, Glasgow coma scale (GCS) on arrival, incident date and time, injured body regions, 30-day mortality, helmet use and intubation rate. Comparison was made between groups of patients based on mechanism of injury. Results: A total of 605 cycling related trauma cases were identified, with 52 being excluded due to incomplete data. The most common mechanism was 'fall from cycle' (53.5%). The 'cyclist v vehicle' group was associated with a significantly higher Injury Severity score (ISS), lower GCS and higher intubation rate. Helmet wearers were significantly older than non-wearers and helmet use was associated with a significantly reduced risk of head injury, lower ISS and intubation rate and a higher GCS. Discussion: With a likely increase in future cycling uptake, it is crucial that effective interventions are implemented to improve the safety of cyclists. The findings of this study may be used to guide any such intervention. A multi-faceted strategy involving driver and cyclist education, effective road infrastructure changes and helmet promotion campaigns specifically targeting the younger generation could be employed.